Inhibition of lysosomal vacuolar proton pump down-regulates cellular acidification and enhances E. coli bactofection efficiency - Akinsola, Rasaq Olajide; Lee, Choon-Weng; Sim, Edmund U. H.; Narayanan, Kumaran (Elsevier, 2021)
Endosomal escape is considered a crucial barrier that needs to be overcome by integrin-mediated E. coli for gene delivery into mammalian cells. Bafilomycin, a potent inhibitor of the H+ proton pump commonly employed to lower endosomal pH, was evaluated as part of the E. coli protocol during delivery. We found an increase in green fluorescent protein expression up 6.9, 3.2, 5.0, 2.8, and 4.5 fold in HeLa, HEK-293, A549, HT1080, and MCF-7 respectively, compared to untreated cells. Our result showed for the first time that Inhibition of lysosomal VATPase enhances E. coli efficiency.